MiR-124 contributes to glucocorticoid resistance in acute lymphoblastic leukemia by promoting proliferation, inhibiting apoptosis and targeting the glucocorticoid receptor. Issue 172 (September 2017) - Liang, Yan-Ni; Tang, Yan-Lai; Ke, Zhi-Yong; Chen, Yue-Qin; Luo, Xue-Qun; Zhang, Hua; Huang, Li-Bin
Graphical abstract: Highlights: The expression of miR-124 increases significantly in glucocorticoid resistant pediatric ALL cells and ALL cell lines. MiR-124 promotes glucocorticoid resistance in ALL by inducing proliferation, inhibiting apoptosis and targeting the NR3C1. MiR-124 may serve as a potential therapeutic target in ALL with GC resistance. Abstract: Acute lymphoblastic leukemia (ALL) is characterized by the accumulation of abnormal lymphoblasts in the bone marrow and blood. Though great progress has been made for improvement in clinical treatment during the past decades, some children with ALL still relapsed. Glucocorticoid (GC) resistance is an important clinical problem for ALL treatment failure. Therefore, further understanding of the mechanism of GC resistance and exploring novel therapeutic strategies are crucial for improving treatment outcome. The reported involvement of microRNAs (miRNAs) in drug resistance implied that deregulated miRNA expression might contribute to GC treatment response of ALL. However, individual miRNAs and their functional mechanisms potentially involved in the GC response are still largely unknown. In the present study, we found that miR-124 was up-regulated in prednisone insensitive human ALL cell line and prednisone-poor response ALL patients. Furthermore, it was found that miR-124 might contribute to GC resistance by promoting proliferation and inhibiting apoptosis of ALL cells. Importantly, we validated that miR-124, targeted and decreased the expression of glucocorticoid receptor (NR3C1), prevented the inhibitory effect of GC in ALL. These findings strongly suggest that miR-124 is critical in poor GC response and may serve as a potential therapeutic target in ALL with poor GC resistance.